Tricobezoares no estômago, duodeno e íleo - Rodrigues, Fransber Rondinelle Araújo (2000)
A 21-year-old girl presents with a 15-day history of epigastric pain and vomiting. Ten days later, constipation and abdominal distension followed. The patient reported similar epigastric pain and vomiting for 6 days last year. A painless epigastric 12-by-8-centimeter tumor was observed on abdominal palpation, and rectal examination revealed an extrinsic tumor compressing anterior rectal wall. Upper digestive endoscopy showed a trichobezoar. Upon laparotomy, one gastric and one duodenal trichobezoar were removed through an anterior gastrotomy. Another one was found 40 centimeters proximal to the ileo-cecal valve and removed through a proximal ileotomy. Trichobezoar is an unspecific disease, which diagnosis is made upon suspicion. Early recognition of bezoars is important because morbidity and mortality rise considerably once complications occur. We illustrate this case to emphasize the need for early recognition and surgical management in order to reduce morbimortality.